Variables Related to Self-Care Behavior of HIV-Infected Children and Youth at Government Hospitals in Bangkok and Its Environs - อังศุเกียรติถาวร สุลีมาศ; เกษมเนตร ลัดดาวัลย์; จินงี่ ประทีป (Disease Control Journal, 2009)
The purposes of this study were 1) to determine internal variables in term of intention, perceived behavior control, actual behavior control and self-responsibility and external variables of social support and social control in prediction of self - care behavior of HIV-infected children and youth receiving HIV care at government hospitals located in Bangkok and its environs, and 2) to examine the interaction between those internal and external variables related to self - care behavior of HIV - infected children and youth receiving HIV care at government hospitals in Bangkok and its environs. The sample group consisted of 155 HIV - infected children and youth, who were 13 - 24 years; 129 children aged13 - 18 years and 26 youth aged 19 - 24 years. All of them were aware of their HIV-infected status and receiving antiretroviral treatment at infectious clinic in three large government hospitals: Siriraj Hospital, Queen Sirikit National Institute of Children Health and Bumras-Naradure Institute. Data collection was conducted by using 8-item instrument to gather information on personal characteristics and to assess research topics regarding variables. Statistical analysis employed descriptive statistics, t - test, one - way analysis of variance, stepwise multiple regression analysis and two - way analysis of variance. The research finding revealed the following: 1. Variables regarding intention, perceived behavior control, self - responsibility and social control could predict the self - care behavior of HIV - infected children and youth for 67.8% 2. Non interaction between internal variables regarding intention, perceived behavior control, actual behavior control and self-responsibility and external variables including social support and social control which may affect the self - care behavior of HIV - infected children and youth.